Cross-Talk between NOK and EGFR: Juxtamembrane and Kinase domain interactions enhancing STAT3/5 signaling in breast cancer tumorigenesis - Yinyin Wang; Bingdong Zhang; Chunhua He; Bo Tian; Sihan Liu; Jianghua Li; Jiayu Wang; Shigao Yang; Bingtao Zhu; Xiaoguang Wang; Zhijie Chang; Chenxi Cao (Translational Oncology)
Epidermal growth factor receptor (EGFR) plays an important role in the regulation of cell proliferation and migration [1]. It forms a homodimer or heterodimer with other ErbB receptor family members to activate downstream signaling. Emerging evidence indicates that the EGFR activity and downstream signaling are regulated by other proteins except its family members during tumorigenesis. Hence, investigating the diverse partnership profiles of EGFR is crucial for elucidating the mechanisms underlying EGFR-mediated actions in tumors, which in turn can guide the development of targeted therapeutic strategies. Here we report that NOK (also known as STYK1), a novel tyrosine kinase cross-talks with EGFR to promote tumorigenesis and metastasis of breast cancer cells. We found that NOK directly interacted with EGFR and formed a heterodimer complex in a manner of cross interaction via their juxtamembrane (JM) domains and kinase domains. Depletion of NOK impaired, but over-expression of NOK increased, the phosphorylation of EGFR. NOK enhanced EGF-induced phosphorylation of STAT3 and STAT5 via its juxtamembrane (JM) domain in promoting the proliferation and migration of breast cancer cells. Overexpression of NOK and EGFR synergistically induced the tumorigenesis of NIH-3T3 normal cells. We demonstrated that co-expression of NOK and EGFR correlated with tumor malignant stages in breast cancer patients. Our finding introduces a new cross interaction manner of EGFR-NOK via juxtamembrane (JM) domains and kinase domains, uncovers a mechanism by which NOK coordinates EGFR to enhance EGF-STAT3/5 signaling during tumorigenesis and metastasis, and proposes a potential strategy for targeting NOK-EGFR in breast cancer treatment.